ESTIMACIÓN NO PARAMÉTRICA DEL PUNTO DE CORTE ASOCIADO A UNA DECISIÓN DIAGNÓSTICA CON ERRORES PONDERADOS - Martínez-Camblor, Pablo (Revista Colombiana de Estadística, 2011)
The study of diagnostic tests is a hot topic which has direct applications in biomedical sciences. Despite of the relevance, in a diagnostic process, of the threshold (or cutoff point) employed on the decision taken by the physician, the study and comparison of the accuracy among different diagnostic criterions has been the main field of study. In this paper, the authors are interested in the study of the involved cutoff point estimation in diagnostic tests with weighted errors. With this goal, a nonparametric smoothed utility function estimator is considered. The bootstrap and the asymptotic distributions for the related M-estimator are derived. Finally, the obtained results are applied to study the Procalcitonin level which determines whether a child within the Pediatric Intensive Care Unit (UCIP) has a virical sepsis.